LASER in periodontal treatment: is it an effective treatment or science fiction? - Theodoro, Letícia Helena [UNESP]; Marcantonio, Rosemary Adriana Chiérici [UNESP]; Wainwright, Mark; Garcia, Valdir Gouveia (FapUNIFESP (SciELO), 2021)
There are several studies that evaluate the use of lasers in periodontal treatment in non-surgical or surgical therapy. However, while several studies showed clinically beneficial effects of some lasers in periodontal treatment, there are few clinical reports of additional advantages of lasers as adjunctive treatments in periodontology. The aim of this paper is to demonstrate and critically analyze the level of scientific evidence of effects of low-level lasers and high-power lasers in periodontology. A narrative review of the studies was carried out in each topic and type of laser or periodontal treatment. In nonsurgical periodontal therapy the results showed that there is an additional clinical benefit when using a diode laser (DL) associated with scaling and root planing (SRP) in patients with moderate to severe periodontitis. The Er:YAG laser seems to be the most suitable for nonsurgical periodontal therapy and promotes the same clinical effects as conventional therapy. In periodontal surgery vaporization of the gingival or mucosal tissue can be carried out with DL, CO2, Nd:YAG, Er:YAG and Er,Cr:YSGG lasers. Photobiomodulation (PBM), mediated by low-level lasers associated with non-surgical periodontal therapy, promotes additional benefits in the short term and accelerates the bone and gingival tissue repair process and also reduces postoperative symptoms of periodontal surgery. The effect of antimicrobial Photodynamic Therapy is relevant in the initial reevaluation periods. Studies have shown controversial results of the use of lasers in periodontics, and this fact may be due to the lack of standard parameters of irradiation in each clinical application.
Keywords: Lasers; Low-Level Light Therapy; Periodontal Diseases; Photochemotherapy